Major Tendencies of Lexical Borrowing from English to Oral Business Nepali: Implications for Translators and Language Teacher - Poudel, Kamal Kumar; Sharma, Netra Prasad (Researcher: A Research Journal of Culture and Society, 2020)
In the present study, words and expressions from English used in Nepali while conducting business transactions orally were counted from a corpus comprising approximately 24,000 words using the "Navigation Pane" in the computer. A total of 875 English words including all repetitions were captured. Analyzing the contextual use-and-usage patterns of the English words from the data text, nine tendencies were identified: varying frequencies of the borrowed words; structural patterns of the loanwords; speaker-influence on hearer responses; brevity of the borrowed words/expressions; morphological simplicity; phonological deviation; borrowing as a need; borrowing as an option; and borrowing as a strategy of avoiding L1 vulgarism or indecency. The implication drawn from the study is important for translators and language teachers: there is no point in artificially translating commonly used loanwords borrowed from English to Nepali in the name of preserving the purity of the Nepali language. Moreover, an area for the English teacher's focus of teaching is the phonologically deviated loanblends.